2021
DOI: 10.1002/adma.202102131
|View full text |Cite
|
Sign up to set email alerts
|

Pangolin‐Inspired Stretchable, Microwave‐Invisible Metascale

Abstract: Microwave‐invisible devices are emerging as a valuable technology in various applications, including soft robotics, shape‐morphing structures, and textural camouflages, especially in electronic countermeasures. Unfortunately, conventional microwave‐absorbing metastructures and bulk absorbers are stretching confined, limiting their application in deformable or special‐shaped targets. To overcome such limitations, a conceptually novel soft–rigid‐connection strategy, inspired by the pangolin, is proposed. Pangoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 57 publications
(14 reference statements)
0
46
0
Order By: Relevance
“…Aside from controlling morphology [ 16–18 ] and electron interactions, [ 19,20 ] the careful design and control of other parameters, such as defect levels, [ 21–23 ] electronic conductivity, [ 24 ] composition features, [ 25–27 ] and interfacial construction, [ 28,29 ] become key factors in engineering EMW absorption properties. To regulate defect levels and electronic conductivity, it has been reported that anion doping (such as N, [ 30 ] S, [ 31 ] and P [ 32 ] ) can improve defect levels by degrading crystal lattice and vacancy formation.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from controlling morphology [ 16–18 ] and electron interactions, [ 19,20 ] the careful design and control of other parameters, such as defect levels, [ 21–23 ] electronic conductivity, [ 24 ] composition features, [ 25–27 ] and interfacial construction, [ 28,29 ] become key factors in engineering EMW absorption properties. To regulate defect levels and electronic conductivity, it has been reported that anion doping (such as N, [ 30 ] S, [ 31 ] and P [ 32 ] ) can improve defect levels by degrading crystal lattice and vacancy formation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] Previous reports have shown that power loss (PL) was positively correlated with the electrical field tangent to the SLUs, while the normal component of the electric field did not contribute to the power loss. [ 36 ] Compared to the solid counterpart, the electric field intensity of the SLUs structure increased by three times and exhibited a specific spatial distribution (Figure 3c). With quantitative analysis, the PL was expressed by: PL=normalΩ12σEfalse|false|2normaldv where σ and E || denote the conductivity of the SLUs and intensity of the tangential electric field, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] Currently, this type of patterning in substrates is largely managed by multistep photolithographic processes at the expense of finely controlling features, which is necessary for tuning a combination of properties. [36,37] Additionally, these complex strategies and costly equipment make such routes less appealing for massproduction compared to the hard-template method.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,3 ] Nowadays, the rapid development of soft robotics, deformable structures, and camouflages boosts the demands for flexible and microwave‐invisible materials in the application of electronic countermeasures and precision equipment protection. [ 4,5 ] Conventional microwave‐absorption materials (MAMs), such as carbon‐based materials (graphene, MXene, carbon nanotubes), [ 6,7 ] metal‐based materials (transition metal oxides/sulfides, alloy), [ 8 ] and conductive polymer [ 9 ] provided super absorption efficiency but very limited controllability and poor processability. Recently, some flexible MAMs have been developed for more complicated target applications, such as metastructures and polymer‐reinforced composites.…”
Section: Introductionmentioning
confidence: 99%